Modeling of Dislocation Grain Boundary Interactions in Gradient Crystal Plasticity Theories - Erdle, Hannes (Schriftenreihe Kontinuumsmechanik im Maschinenbau, 2022)
A physically-based dislocation theory of plasticity is derived within an extended continuum mechanical context. Thermodynamically consistent flow rules at the grain boundaries are derived. With an analytical solution of a three-phase periodic laminate, dislocation pile-up at grain boundaries and dislocation transmission through the grain boundaries are investigated. For the finite element implementations, numerically efficient approaches are introduced based on accumulated field variables.